MET-targeted therapies for the treatment of non-small-cell lung cancer: A systematic review and meta-analysis - Xu, Linrui; Wang, Faping; Luo, Fengming (Frontiers in Oncology, 2022)
Background: Dysregulation of the mesenchymal epithelial transition (MET) pathway contributes to poor clinical outcomes in patients with non-small cell lung cancer (NSCLC). Numerous clinical trials are currently investigating several therapies based on modulation of the MET pathway. Objectives: This study aimed to systematically evaluate the activity and safety of MET inhibitors in patients with NSCLC. Methods: We searched PubMed, Embase, and the Cochrane Library from inception to June 02, 2022. The objective response rate (ORR) and disease control rate (DCR) were extracted as the main outcomes and pooled using the weighted mean proportion with fixed- or random-effects models in cases of significant heterogeneity (I2>50%). Safety analysis was performed based on adverse events reported in all studies. Results: Eleven studies (882 patients) were included in the meta-analysis. The pooled ORR was 28.1% (95% confidence interval [CI], 0.223–0.354), while the pooled DCR was 69.1% (95% CI, 0.631–0.756). ORRs were higher for tepotinib (44.7% [95% CI, 0.365–0.530]) and savolitinib (42.9% [95% CI, 0.311–0.553]) than for other types of MET inhibitors. Patients with NSCLC with exon 14 skipping exhibited higher ORRs (39.3% (95% CI, 0.296–0.522)) and DCRs (77.8% (95% CI, 0.714–0.847)) than those with MET protein overexpression or amplification. Intracranial response rate and intracranial disease control rates were 40.1% (95% CI, 0.289–0.556) and 95.4% (95% CI, 0.892–0.100), respectively. Adverse events were mild (grade 1 to 2) in 87.2% of patients. Common adverse events above grade 3 included lower extremity edema (3.5% [95% CI, 0.027–0.044]), alanine aminotransferase (ALT) elevation (2.4% [95% CI, 0.014–0.033]), and lipase elevation (2.2% [95% CI, 0.016–0.031]). Conclusion: MET inhibitors, which exhibited a satisfactory safety profile in the current study, may become a new standard of care for addressing MET dysregulation in patients with advanced or metastatic NSCLC, and even in those with brain metastases, particularly tepotinib, savolitinib and capmatinib. Further randomized trials are required to establish standard predictive biomarkers for MET therapies and to compare the effects of different MET inhibitors in NSCLC with MET dysregulation.